Corporate communication with artificial intelligence: GAD Chone and Manta Cases - Coveña Chica, Mary Carmen (2024)
This article aims to analyze the integration of artificial intelligence (AI) in the corporate communication of the Decentralized Autonomous Governments (GADS) of the Chone and Manta Cantons, Ecuador. A mixed methodology was used, with structured interviews and content analysis, focused on the months of May, June and July 2023. The research explored the integration of AI, and the platforms used for content creation were identified, evaluating the interaction with the audience. It was found that AI is applied in graphic design, audiovisual production and writing, increasing notoriety, optimizing time and improving the quality of content. Technologies such as Midjourney, Photoshop and Leonardo.IA are used to automate tasks, increasing productivity, although they face training and adaptation challenges. The study concludes that the incorporation of AI has generated significant changes in corporate communication. Despite the low proportion of AI-generated content at the time of the research, the interaction is promising. The main challenge is to balance automation with the integrity of the content, ensuring ethical communication supported by the human factor.